Sistem Perbaikan Kata Tidak Baku Bahasa Indonesia Menggunakan Metode Crowdsourcing - Danny Sebastian; Kristian Adi Nugraha (Maranatha University Press, 2019)
Most languages have two form of words: standard and not-standard. Standard words usually used in formal conversation, while not-standard words used in informal conversation. The massive use of non-standard words in the text-based communication through social media application causing a new problem for its text-processing features such as language translator or artificial intelligence (AI) conversation program (chatbots). Our research purpose is to create a system that can convert any non-standard Indonesian word into standard Indonesian word using crowdsourcing method, a community-based method to create database that contain non-standard Indonesian words and its associated standard words. We hope this system can help people who working on text-mining based application, especially in Indonesian words, to improve their performance in text-processing.